1985
DOI: 10.1159/000145932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Increases in Body Weight on the Growth of Limb Bones in Hypophysectomized Rats

Abstract: The purpose of this study was to subject groups of hypophysectomized male and female rats each to a simulated specific 10% increase in body weight, to a maximum of a doubling of body weight, in order to study the effects of quantified, increased, intermittent, compressive forces on limb bone growth. Chronic centrifugation was employed. 21-day-old Sprague-Dawley rats were used. After 60 days of centrifugation, the rats were sacrificed. The humerus, radius, ulna, femur and tibia were removed from each animal, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…1984a] suggested that the value of g and the time spent at centrifugation are both significant factors in the effects of simulated increases in body weight on limb bone growth. In our second study using constant centrifugation, male and female hypophysectomized weanling rats were used [Simon et al, 1984b], The results of that study suggested that simulated in creases of body weight within the range of 1.1-2.0 g produced enhanced bone growth, in absolute values. This result was especially significant, considering that the control animals had a statistically significant (p <0.05) greater body weight than any of the experi mental animals.…”
Section: Introductionmentioning
confidence: 99%
“…1984a] suggested that the value of g and the time spent at centrifugation are both significant factors in the effects of simulated increases in body weight on limb bone growth. In our second study using constant centrifugation, male and female hypophysectomized weanling rats were used [Simon et al, 1984b], The results of that study suggested that simulated in creases of body weight within the range of 1.1-2.0 g produced enhanced bone growth, in absolute values. This result was especially significant, considering that the control animals had a statistically significant (p <0.05) greater body weight than any of the experi mental animals.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of recent investigations in this laboratory, groups of rats were subjected to centrifugation within the range 1.1-2.0 g [Simon et al, 1984[Simon et al, . 1985a.…”
Section: Introductionmentioning
confidence: 99%